Factors associated with anemia in trimester III pregnant women - Majidah, Andini; Maryani, Tri; Meilani, Niken (Jurnal Kesehatan Ibu dan Anak, 2018)
The anemia incidence rate of Yogyakarta City has continued to increase since 2013 until 2015 and the highest ranking in DIY province in 2015 is 32.39%.Several studies have shown that independent predictors of anemia in pregnant women, aged 15-24, family> 5, multigravida, low income, current clinical illness, intestinal parasite infection, no history of contraceptive use, third trimester pregnancy, bleeding over-menstruating and low body mass index.But there are still differences from several studies. This study was to know knowledge of factors associated withanemia in trimester III pregnant women in Yogyakarta 2017. This was an observational analytic study withcross sectionaldesignon 107 trimester pregnant women in Pakualaman Public Health Centre, Jetis Health Center and Matrijeron Health Center of Yogyakarta City withpurposive sampling technique.The data analysis used chi squaretest. The Results f this study was the variables with no significant association with anemia were maternal age (p = 0.243), education (p = 0.208), income (0.533), and adherence to tablet Fe (p = 0.378). Multivariate analysis showed that pregnant women with parity 2-3 3 times more at risk of anemia in third trimester than pregnant women with parity <1 (95% CI 1,135-8,183). Conclusion: Parity is the most dominant factor in relation to the incidence of anemia in pregnant women trimester III.